Analisis Loyalitas Pelanggan Di BTKLPP Kelas I Palembang - Nurul Fadillah (Jurnal Kesehatan Saelmakers PERDANA, 2022)
BTKLPP Class I Palembang is a central government agency where one of the main tasks and functions is to provide health services. Health service providers are required to always provide good service to improve the quality of their services so that customer trust is always given to health service providers so that it can have an impact on customer satisfaction and loyalty. This is also important regarding the existence of competitors or competitors who provide similar services. This study aims to analyze the determinants of service quality and customer satisfaction on customer loyalty in BTKLPP Class I Palembang. The research design used is descriptive research with a cross-sectional approach. The population in this study are all customers or consumers who have used the services of BTKLPP Class I Palembang in 2021, then the research sample was obtained from the results of calculations using the Slovin formula as many as 100 samples. The results showed that there was a significant relationship between service quality and customer satisfaction on customer loyalty (p-value = 0.000) with a service quality correlation coefficient value of 0.654 and a customer satisfaction correlation coefficient of 0.711, meaning that an increase in the value of service quality and customer satisfaction will increase the value of customer loyalty. Based on the results of statistical testing in this study, it was found that only Customer Satisfaction had a partial effect on Customer Loyalty (p-value = 0.000), while Service Quality had no partial effect on Customer Loyalty (p-value > 0.05). Service Quality and Customer Satisfaction simultaneously affect customer loyalty by 48.2%, while the remaining 51.8% is the influence of other factors outside of this study.